2009
DOI: 10.1073/pnas.0809688106
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral visual field maps in a patient with only one hemisphere

Abstract: In mammals smooth retinotopic maps of the visual field are formed along the visual processing pathway whereby the left visual field is represented in the right hemisphere and vice versa. The reorganization of retinotopic maps in the lateral geniculate nucleus (LGN) of the thalamus and early visual areas (V1-V3) is studied in a patient who was born with only one cerebral hemisphere. Before the seventh week of embryonic gestation, the development of the patient's right cerebral hemisphere terminated. Despite the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
73
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(90 citation statements)
references
References 48 publications
11
73
6
Order By: Relevance
“…For example, damage to the primary visual cortex (V1) in an adult leads to blindness through production of a scotoma; however, during infancy the magnitude of the deficits can be greatly attenuated and there is significant sparing of vision. This phenomenon has been observed in both humans (Lambert et al 1987;Kiper et al 2002;Filan et al 2006;Werth, 2006;Muckli et al 2009) and non-human primates (Rodman et al 1993;Moore et al 1995Moore et al , 1996. Interestingly, damage to the occipital region of the neocortex, which includes V1, is a common occurrence as a result of a stroke, neurotrauma, disease or hypoxia in perinates.…”
Section: Childhood Lesions Of the Visual Cortexmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, damage to the primary visual cortex (V1) in an adult leads to blindness through production of a scotoma; however, during infancy the magnitude of the deficits can be greatly attenuated and there is significant sparing of vision. This phenomenon has been observed in both humans (Lambert et al 1987;Kiper et al 2002;Filan et al 2006;Werth, 2006;Muckli et al 2009) and non-human primates (Rodman et al 1993;Moore et al 1995Moore et al , 1996. Interestingly, damage to the occipital region of the neocortex, which includes V1, is a common occurrence as a result of a stroke, neurotrauma, disease or hypoxia in perinates.…”
Section: Childhood Lesions Of the Visual Cortexmentioning
confidence: 99%
“…A. Bourne Rakic, 1999), and would probably have a role in the increased plasticity observed. Muckli et al (2009) reported on a single case study of a 10-year-old girl (AH) who lacked her entire right hemisphere and most of her right eye (microphthalmus) from birth but remarkably had close to normal vision in both hemifields. In subject AH it was demonstrated that, despite the complete loss of her right hemisphere, the patient's remaining hemisphere has not only developed maps of the contralateral visual hemifield but, surprisingly, also maps of the ipsilateral visual hemifield.…”
Section: Mechanisms Of Recovery In Children With Cortical Visual Lesionsmentioning
confidence: 99%
“…Consequently, the left visual hemifield is represented on the right hemisphere and vice versa. In patients with congenital malformations of the optic chiasm there can be reduced crossing of nasal axons, as reported for achiasma and hemihydranencephaly (Apkarian et al, 1994;Victor et al, 2000;Muckli et al, 2009;Hoffmann et al, 2012;Fracasso et al, 2016), or additional crossing from the temporal axons, as evident for albinism. In fact, the latter has been regarded to be pathognomonic, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Abnormal visual development can modify these retinotopic maps [2][3][4][5] . Under circumstances where individuals acquire early visual experience in the presence of a lesion to the center of the retina, reorganization of the visual representation occurs 6 .…”
Section: Introductionmentioning
confidence: 99%